2021
DOI: 10.17336/igusbd.655890
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık Örgütlerindeki Vizyoner Liderlik Özelliklerinin Örgütsel Çeviklik Üzerine Etkisi; İstanbul İli Bakırköy İlçesindeki Özel Hastanelerde Bir Uygulama

Abstract: In this study, a field research was conducted to determine the effect of visionary leadership on organizational agility. The data of the analysis were obtained from the health care workers working in private hospitals in the Bakirkoy region by the survey method and 200 questionnaires were analyzed statistically. To achieve the results, reliability analysis, correlation analysis and regression analysis were performed. In the conclusion part, it is confirmed that there is a parallel and meaningful relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…It was also found that sub-dimensions of visionary leadership have a significant effect on competence and speed, which are organizational agility sub-dimensions. In the study titled " The effect of visionary leadership characteristics on organizational agility in health organizations; An Application in private hospitals in Bakirkoy District of Istanbul Province" conducted by Tamer (2021) with 200 personnel working in private hospitals in Istanbul, it was determined that visionary leadership positively affects organizational agility. It was also found that the subdimensions of visionary leadership have a meaningful effect on competence and flexibility, which are the sub-dimensions of organizational agility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that sub-dimensions of visionary leadership have a significant effect on competence and speed, which are organizational agility sub-dimensions. In the study titled " The effect of visionary leadership characteristics on organizational agility in health organizations; An Application in private hospitals in Bakirkoy District of Istanbul Province" conducted by Tamer (2021) with 200 personnel working in private hospitals in Istanbul, it was determined that visionary leadership positively affects organizational agility. It was also found that the subdimensions of visionary leadership have a meaningful effect on competence and flexibility, which are the sub-dimensions of organizational agility.…”
Section: Discussionmentioning
confidence: 99%
“…Ozeroglu and Kocyigit (2020) mentioned that visionary leadership has a positive effect on organizational agility. Finally, Tamer (2021) stated in his study that visionary leadership positively affects organizational agility.…”
Section: The Relationship Between Visionary Leadership and Organizati...mentioning
confidence: 98%
“…Although the general purpose of individuals who take part in health tourism is to tend to be healthy, lots of different classifications of health tourism have been stated to group and identify the individuals taking part in health tourism for different purposes and quests, but no common decision has been reached on classification. Reviewing the studies conducted in the literature (Tengilimoğlu, 2013;Tamer, 2020), it has been seen that health tourism is classified into four headings. The sub-headings in this classification are; thermal tourism, SPA-Wellness tourism, Third-age tourism and medical tourism.…”
Section: The Concept and Classification Of Health Tourismmentioning
confidence: 99%